2016
DOI: 10.1016/j.jaap.2016.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes synthetized from gaseous products of waste polymer pyrolysis and their application

Abstract: 14This work is dedicated to the synthesis of carbon nanotube from pyrolysis gases obtained by plastics. Virgin and 15 waste plastics (polyethylene, polypropylene, polystyrene, polyamide, polyvinyl-chloride, municipal plastic waste) 16were used as raw materials and fed into a horizontal tubular reactor and pyrolyzed without catalyst at 560-570°C. 17Raw materials could be transformed into 14-32% gases and 15-44% pyrolysis oils, depending on the type of raw 18 materials. Pyrolysis of municipal plastic waste produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 28 publications
1
41
0
Order By: Relevance
“…Considering the unwanted nature of the generation of these carbon deposits, the economic throughput of the H2 production process from hydrocarbons may be enhanced by means of the production of value-added carbon materials ( Figure 17). For instance, char is reported in the literature as a promising precursor for graphene production [305,306], whereas the coke deposited on the catalyst (catalytic routes) may be in the form of carbon nanotubes [307,308], whose morphology shows multiple favorable applications [309].…”
Section: Figure 17mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the unwanted nature of the generation of these carbon deposits, the economic throughput of the H2 production process from hydrocarbons may be enhanced by means of the production of value-added carbon materials ( Figure 17). For instance, char is reported in the literature as a promising precursor for graphene production [305,306], whereas the coke deposited on the catalyst (catalytic routes) may be in the form of carbon nanotubes [307,308], whose morphology shows multiple favorable applications [309].…”
Section: Figure 17mentioning
confidence: 99%
“…Correlation diagram between the factors influential on deactivation during the steam reforming of bio-oil on a Ni/La2O3-αAl2O3 catalyst. Adapted from [(a) TEM image of a Ni particle[349]; (b) SEM image of synthetized CNTs[309]; (c) TEM image of a conical CNF[361]. Techniques for the characterization of coke deposited on reforming catalysts.Information providedSurface area and porosity of coke and coked catalyst Coke morphology and location Coke morphology, dimensions and location Content; qualitative location and composition; model-based combustion kinetics Content; Production of carbon materials in the main H2 production processes from hydrocarbon and oxygenate feedstock.…”
mentioning
confidence: 99%
“…The catalytic pyrolysiso fp lastics provides an environmentally friendly and inexpensive strategy for treatment of aw ide range of plastic waste, which can be used as carbon precursors. [16] Carbon nanotubes have au nique structure with particular stabilitya nd excellent electrical conductivity,s ot hey can be applieda ss tructure reinforcements, [17] or in further electrochemicala pplicationss uch as the productiono fs upercapacitors. [18] Although carbon-based materials derived from plastics have attracted widespread attentionr ecently,t heir application to ORR catalysis is rarely reported.V eksha et al [19] reported some attempts at electrocatalytic applications,a nd the CNT electrocatalysts prepared directly from plastic are not as good as commercial Pt/C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained by Borsodi et al . showed that the presence of Cl (0.3 wt% PVC in waste HDPE) had an adverse effect on CNT formation, whereas the presence of S had less influence with respect to CNT morphologies . El Essawy et al .…”
Section: Promising Approachesmentioning
confidence: 99%
“…99 Results obtained by Borsodi et al showed that the presence of Cl (0.3 wt% PVC in waste HDPE) had an adverse effect on CNT formation, whereas the presence of S had less influence with respect to CNT morphologies. 102 El Essawy et al reported a cost-efficient solvent-free procedure to convert PET bottles into carbon nanomaterials through thermal dissociation inside a closed system under autogenic pressure in the presence of additives and/or catalyst, which acted as cluster nuclei for carbon nanomaterials like CNTs and fullerenes. This study was successful in the production and control of the different forms of micro-structured carbon nanomaterials from PET waste through optimization of parameters with regard to amount of catalyst, additives and time.…”
Section: Synthesis Of Carbon Microspheres and Nanotubes From Plastic mentioning
confidence: 99%